Rola Żydów z byłego Związku Radzieckiego w kształtowaniu stosunków izraelsko-polskich - Szydzisz, Marcin (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2013)
The Jews from the former Soviet Union states constitute a group of Israelites of about a million people. Generally, this community knows Poland quite well and is interested in it. Unfortunately this interest does not translate into a concrete concept of relations with our country. Either in programmes of political parties or on Russian-language internet portals there is no information on how the relations between our countries should be managed. In this article the author gives some recommendations in an attempt to find the way of mutual contacts revival.
Keywords: polityka wschodnia; Ukraina; Federacja Rosyjska; Unia Europejska; NATO; relacje polsko-ukraińskie; stosunki polsko-rosyjskie; Kościół katolicki; Kościół Prawosławny; dyplomacja publiczna; bezpieczeństwo; Katyń